PRINCIPLE OF EQUALITY BEFORE THE LAW AND DIVERSION ON CRIMINAL JUSTICE SYSTEM FOR CHILDREN IN INDONESIA - SUPENO, BAMBANG JOYO (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2020)
Restorative justice is the ultimate goal of Law Number 11 of 2012 concerning the Criminal Justice System for Children, so that children in conflict with the law must obtain Diversion. Article 7 paragraph (2) and Article 9 paragraph (2) the SPPA Law isdiscriminatory and unjust, both for perpetrators and victims of criminal acts, because there are restrictions, exceptions and disregard for Diversion provisions. In concretto, in 2014-2018 the use of Diversion (49.61%) was lower than formal justice (50.39%), the data showed that some children who were in conflict with the law did not get Diversion. Based on the analysis of concept the principle of equality before the law in ideal-norm thinking, it is necessary to reconstruct the provisions of Diversion in the SPPA Law, namely (a) The principle of equality before the law must be used as a determining indicator in the formulation and process of Diversion law enforcement. (b) Provisions on child-oriented Diversion as the subject of criminal acts will determine justice in the application of Diversion for every child in conflict with the law. (c) Diversion provisions which are oriented towards acts, sanctions and value of losses as a requirement for the application of Diversion, will cause discrimination in the application of Diversion.